The Effect of Career Adaptability on Career Anxiety with the Mediation of Self-Efficacy in Decision-Making in UNESA Business Education Students - Lailatul Badriyah; Dwi Yuli Rakhmawati (Economic Education Analysis Journal, 2026)
This study examines the relationship between career adaptability and career anxiety through the mediating role of career decision-making self-efficacy among undergraduate business education students. Drawing on Career Construction Theory and Social Cognitive Career Theory, the study addresses the limited understanding of how adaptive career resources are translated into reduced career anxiety through confidence in career decision-making. A quantitative explanatory design was employed, and all members of the target population were included to ensure comprehensive representation of the study context. Data were collected using a structured questionnaire and analyzed through path analysis. The findings demonstrate that career adaptability reduces career anxiety both directly and indirectly through career decision-making self-efficacy. Students with stronger adaptive capacities tend to develop greater confidence in making career decisions, which subsequently alleviates career-related anxiety. This study extends career development literature by clarifying the psychological mechanism linking adaptability and anxiety, while offering practical implications for higher education institutions in designing interventions that strengthen students’ career readiness, decision-making confidence, and resilience in navigating an increasingly uncertain labor market.